Usage of Facebook in Education - Meena (JOURNAL OF INDIAN EDUCATION, 2015)
The conventional set up of four walls with three dimensional teaching aids or smart classrooms are shaking under the regime of Social Networking Sites (SNS) where students are making connections with the unexplored outer world. The educational relevance of the Facebook in contemporary educational system is demanding our immediate attention. The undeterred task ahead for teachers, students, policy makers and administrators is to take this challenge on priority basis without ignoring the time gap that education and technology will contour for the education of future generations. The present paper explores the possibilities of usage of Facebook in education for teachers via case studies. The positive results of the cases discussed here in the paper are encouraging and motivating.